Multipurpose optical setup for studying radiation-induced transformations of metals and alloys surface - Belyaeva, A. I.; Galuza, A. A.; Kolenov, I. V.; Savchenko, A. A. (National Science Center "Kharkiv Institute of Physics and Technology", 2014)
A multipurpose optical setup for studying radiation-induced transformations of metals and alloys surface and optical properties of transparent objects is developed and created. The setup scheme is justified and the results of its verification are given.

Розроблено та реалізовано багатофункціональний оптичний комплекс для дослідження радіаційних перетворень на поверхні металів і сплавів, а також оптичних характеристик прозорих тіл. Обґрунтовано схему комплексу та наведено результати його тестування.
Багатофункціональний оптичний комплекс для дослідження радіаційних перетворень на поверхні металів і сплавів
Keywords: surface state; techniques to study; optical techniques; microscopy; reflectometry; ellipsometry; interferometry; радіаційні перетворення; поверхні металів; поверхні сплавів